2008
DOI: 10.1126/science.1152725
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Host Proteins Required for HIV Infection Through a Functional Genomic Screen

Abstract: HIV-1 exploits multiple host proteins during infection. We performed a large-scale small interfering RNA screen to identify host factors required by HIV-1 and identified more than 250 HIV-dependency factors (HDFs). These proteins participate in a broad array of cellular functions and implicate new pathways in the viral life cycle. Further analysis revealed previously unknown roles for retrograde Golgi transport proteins (Rab6 and Vps53) in viral entry, a karyopherin (TNPO3) in viral integration, and the Mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

52
1,382
4
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,315 publications
(1,446 citation statements)
references
References 35 publications
52
1,382
4
8
Order By: Relevance
“…[26][27][28][29][30][31][32][33][34][35] Multiple screens for HIV-1 inhibitors relied on in vitro assays, which used viral proteins or their fragments, or on HIV-1 infections/replication as a readout. In vitro screening has identified competitive inhibitors of assembly of the gp41 HR1-and HR2-derived peptides into the 6HB.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][35] Multiple screens for HIV-1 inhibitors relied on in vitro assays, which used viral proteins or their fragments, or on HIV-1 infections/replication as a readout. In vitro screening has identified competitive inhibitors of assembly of the gp41 HR1-and HR2-derived peptides into the 6HB.…”
Section: Introductionmentioning
confidence: 99%
“…This is also incorporated into our database, allowing us to see which HIV proteins are known to be associated with any of our screening hits, together with the nature of the interaction and the evidence for it. Similarly, the collections of host factors described in previous published HIV screens [4][5][6] have been mined from the papers and added to the database, allowing direct comparison of the degree of overlap and gene composition of the various studies with each other and with our screens.…”
Section: Interaction Networkmentioning
confidence: 99%
“…Since the rate of mutations of cellular genes is substantially lower than for viral genomes, the particular benefit of targeting host factors is that it may provide a higher barrier to the generation of anti-drug resistance. A most powerful and versatile approach to identify such potential cellular interaction partners of HIV-1 are RNAi-based loss-of-function screens, as suggested by very recent reports [4][5][6].…”
mentioning
confidence: 99%
“…The first screen to be published was performed in cultured human HeLa cells expressing CD4 as the essential receptor for HIV-1 entry [58]. The goal was to identify host proteins involved in early events of infection such as virus entry, uncoating, reverse transcription, integration and viral gene expression as well as factors needed for late stages in infection such as viral assembly and release.…”
Section: Rnai Screens To Identify Host Factors That Influence Viral Imentioning
confidence: 99%
“…The goal was to identify host proteins involved in early events of infection such as virus entry, uncoating, reverse transcription, integration and viral gene expression as well as factors needed for late stages in infection such as viral assembly and release. Considering more than 21 000 genes, Brass et al [58] identified 273 host factors required for HIV-1 replication. Preliminary characterization of three of the genes revealed previously unknown functions: Rab6, which is involved in the retrograde transport from endosomes to the Golgi and from the Golgi to the ER, was shown to be important for virus entry.…”
Section: Rnai Screens To Identify Host Factors That Influence Viral Imentioning
confidence: 99%